2017
DOI: 10.1021/acs.jproteome.7b00191
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Extracellular Matrix of Normal and Diseased Tissues Using Proteomics

Abstract: The extracellular matrix (ECM) is a complex meshwork of insoluble fibrillar proteins and signaling factors interacting together to provide architectural and instructional cues to the surrounding cells. Alterations in ECM organization or composition and excessive ECM deposition have been observed in diseases such as fibrosis, cardiovascular diseases, and cancer. We provide here optimized protocols to solubilize ECM proteins from normal or tumor tissues, digest the proteins into peptides, analyze ECM peptides by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
181
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(186 citation statements)
references
References 30 publications
4
181
0
1
Order By: Relevance
“…These data suggested that, within CRC, lymphatics might shape the architecture of cancer‐associated ECM and regulate tumor growth. This is consistent with previous studies demonstrating that ECM‐lymphatic interactions, along with biophysical characteristics of the stroma, may have consequences for tumor growth and progression …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These data suggested that, within CRC, lymphatics might shape the architecture of cancer‐associated ECM and regulate tumor growth. This is consistent with previous studies demonstrating that ECM‐lymphatic interactions, along with biophysical characteristics of the stroma, may have consequences for tumor growth and progression …”
Section: Resultssupporting
confidence: 93%
“…This is consistent with previous studies demonstrating that ECM-lymphatic interactions, along with biophysical characteristics of the stroma, may have consequences for tumor growth and progression. 11,12 The ECM protein repertoire, termed the "matrisome," is composed of structural proteins, such as fibronectins, collagens, laminins and proteoglycans, but also by soluble growth factors and cytokines, thus establishing a dense network that assists functions ranging from cell proliferation, adhesion and motility to cell signaling. 13 Therefore, to elucidate whether intestinal LVs could shape the core matrisome in locally advanced CRC, eventually influencing tumor growth, we analyzed RNA-seq data with attention on matrisome compartmentrelated genes, 13 and we observed the expression of many of these genes to be significantly upregulated in CRC-HILEC in comparison with healthy controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For proteomic analysis of the same biopsies we focused on the ECM and associated molecules using a method that enriches whole tissue lysates for the matrisome protein compartment (16). Using this technique we detected 145 proteins (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Using our matrisome-focused proteomic technique (16) and the RNAseq data we quantitatively assessed matrisome proteins and genes. In terms of relative mass ratios, the major matrix proteins in samples with the lowest disease score were collagen 1, 6 and 3, the glycoprotein fibrillin, the ECM regulator alpha-2-macroprotein, and the basement membrane proteoglycans lumican and heparin sulphate proteoglycan-2.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing knowledge of which cell populations are present in a tumor (Lee et al, 2017; Heindl et al, 2015; Yuan, 2016; Carmona-Fontaine et al, 2017) and the physical matrix in which these cells reside (Naba et al, 2017; Pearce et al, 2018). However, less is known about the soluble environment of tumors, such as the nutrients that are present in the extracellular compartment within tumors.…”
Section: Discussionmentioning
confidence: 99%